Efficacy and safety of novel and repurposed drugs for the treatment of drug-resistant tuberculosis - Olayanju, Olatunde (Department of Medicine, 2020)
Background: There is widespread concern about the rise of drug-resistant TB because treatment outcomes of affected patients remain poor and treatment options are limited. After more than a forty-year gap without any breakthrough discovery, several new (bedaquiline and delamanid) and repurposed drugs (linezolid) are increasingly becoming available for use. However, data regarding the efficacy and safety of these drugs in drug-resistant TB patients, with or without HIV infection, from a real-life programmatic setting are lacking. This thesis aims to address that knowledge gap and provide information for management of drug-resistant TB in countries with high disease burden. Methods: A total of 326 drug resistant TB patients were prospectively followed up between January 2008 and April 2018. The efficacy and safety of two new drugs (bedaquiline and delamanid) and one repurposed drug (linezolid) was determined in these patients in three studies. In the first study, 24 months treatment outcomes and adverse event profiles were compared between extensively drug resistant (XDR) TB patients who received programmatic treatment regimens with the backbone of second line injectables and fluoroquinolones (nonbedaquiline-based) and those who received a bedaquiline- and/ or linezolid-based treatment regimen. The second study determined the frequency of system-specific adverse events associated with linezolid. The third study interrogated the safety and effectiveness of a strengthened treatment regimen containing a combination of delamanid and bedaquiline in patients with poor prognostic features compared to bedaquiline-based regimen. Results: In the first study, patients who received a bedaquiline-based treatment regimen had a significantly greater favourable outcome rate (66.2% vs 13.2%; p<0.001) ), more than a fourfold reduction in treatment failure rate (5.9% vs 26%; p<0.001 ) and less than a half of mortality rate compared to patients who received a non-bedaquiline-based regimen. The bedaquiline survival and favourable outcome effect remained significant in HIV-infected patients (p<0.001). The second study showed that linezolid interruption was common in patients receiving a bedaquiline-based treatment regimen, and that system-specific toxicity occurred within predictable time frames. It also showed that anaemia (77.3% versus 7.3%; p<0.001), peripheral neuropathy (63.6% versus 14.6%; p=0.003), and optic neuritis (18.2% versus 9.8%; p=0.34) occurred more frequently in linezolid interrupters than in non-interrupters. The third study showed that the use of delamanid-bedaquiline combination regimen was safe and efficacious in drug resistant TB patients with poor prognosis when compared with outcomes in the less sick patients who received a bedaquiline-based regimen. It also showed no significant difference in culture conversion rate at 6 months (92.5% versus 81.8%; p=0.26) or favourable treatment outcome rate (63.4% versus 67.5%; p=0.66) between the two groups. Although patients who received the combination regimen had more frequent occurrence of QTcF prolongation greater than 60 ms from baseline (p=0.001) and more episodes of QTcF greater than 450 ms during treatment (p=0.001), none of them were symptomatic or had delamanid or bedaquiline withdrawn from their regimen. Conclusion: These data demonstrated that new and repurposed drugs remarkably improved treatment outcomes in patients with drug-resistant TB. Although linezolid, which is an important component of the bedaquiline-based treatment regimen, is often associated with system-specific adverse events, these occurred at predictable time frames thereby guiding physicians to make informed management decisions. Lastly, drug resistant TB patients with poor prognosis may benefit from a regimen containing delamanid and bedaquiline which seems relatively safe from an adverse event perspective. These data, despite some limitations, make a case for a widespread and accelerated roll-out of new and repurposed drugs for the treatment of drug resistant TB.